Higher morale is associated with lower risk of depressive disorders five years later among very old people. (March 2017) - Niklasson, Johan; Näsman, Marina; Nyqvist, Fredrica; Conradsson, Mia; Olofsson, Birgitta; Lövheim, Hugo; Gustafson, Yngve
Highlights: Higher morale seems associated with lower risk of depressive disorders 5 years later in very old people. The PGCMS seems to identify very old individuals at risk of depressive disorders 5 years later. High morale could be seen as a salutogenic factor. Abstract: Objective: The aim of this study was to investigate whether higher morale, i.e. future-oriented optimism, at baseline was associated with lower risk of depressive disorders five years later among very old people.Methods The Umeå85+/GErontological Regional Database, a population-based study with a longitudinal design, recruited participants in Sweden and Finland aged 85, 90 and ≥95 years. The sample in the present study included 647 individuals (89.1 ± 4.4 years (Mean ± SD), range 85–103). After five years, 216 were alive and agreed to a follow-up (92.6 ± 3.4 years, range 90–104). The Philadelphia Geriatric Center Morale Scale (PGCMS) was used to assess morale. The depressive disorder diagnosis was determined according to DSM-IV based on medical records and interview data including assessment scales for depressive disorders. A number of sociodemographic, functional and health-related variables were analysed as possible confounders.Results For those with no depressive disorders at baseline, the only baseline variable significantly associated with depressive disorders five years later was the PGCMS score. A logistic regression model showed lower risk of depressive disorders five years later with higher baseline PGCMS scores (odds ratio 0.779 for one point increase in PGCMS, p < 0.001). The association remained after adjusting for social isolation (p < 0.1 association with depressive disorders five years later).Conclusion Our results indicate that the higher the morale, the lower the risk of depressive disorders five years later among very old people. The PGCMS seems to identify those very old individuals at increased risk of depressive disorders five years later. Preventive measures could befocused on this group.